Nucleocytoplasmic mRNP export is an integral part of mRNP biogenesis - Björk, Petra (Springer-Verlag, 2010)
Nucleocytoplasmic export and biogenesis of mRNPs are closely coupled. At the gene, concomitant with synthesis of the pre-mRNA, the transcription machinery, hnRNP proteins, processing, quality control and export machineries cooperate to release processed and export competent mRNPs. After diffusion through the interchromatin space, the mRNPs are translocated through the nuclear pore complex and released into the cytoplasm. At the nuclear pore complex, defined compositional and conformational changes are triggered, but specific cotranscriptionally added components are retained in the mRNP and subsequently influence the cytoplasmic fate of the mRNP. Processes taking place at the gene locus and at the nuclear pore complex are crucial for integrating export as an essential part of gene expression. Spatial, temporal and structural aspects of these events have been highlighted in analyses of the Balbiani ring genes.